Characterization and Analysis of Oil Palm Empty Fruit Bunch (OPEFB) Waste of PT Kharisma Alam Persada South Borneo - Nur Hidayah; Ikna Urwatul Wusko (Majalah Obat Tradisional, 2020)
Empty oil palm bunches are the largest solid waste produced from the palm oil industry processing. In processing 1 ton of fresh palm oil bunches, 230 Kg of empty palm oil bunches will be produced. Based on previous research, it is known that oil palm empty fruit bunches waste is proven to have a large amount of organic mass such as cellulose, hemicellulose, lignin. Organic content as mentioned is rich in benefits so that it can be used as raw material for making daily needs products ranging from food to complementary products such as household appliances, clothing and so on. For this reason, a study was conducted on the content of oil palm empty bunches originating from waste at PT. Kharisma Alam Persada. The characterization process was carried out using the SNI method 0128911992. From the research carried out it was found that the cellulose, hemicellulose and lignin content were 55.75%; 28.93% and 15.32% respectively. So that it is possible to be used as raw material for processing other products.